Coping and Self-Medication in a Community Sample of Junior High School Students - Geneviève Bianca V Bedard; Graham J Reid; Patrick J McGrath; Christine T Chambers (Pain Research and Management)
OBJECTIVE: To examine differences between high and low catastrophizers in terms of pain, self-medication, coping, age and sex.